Behavior of Post Partum Mothers About Baby Massage at Sally Clinic Medan in 2023 - Widia Astuti Tanjung; Karsana Karsana (Healthy-Mu Journal, 2023)
Every parent expects their children to grow and develop optimally, so that they can become qualified and resilient human resources. Baby massage can increase weight, baby growth, baby's endurance and strengthen the love between parents and children. This study is analytic in nature, namely to determine the behavior of pregnant women about baby massage. The research was conducted at the Sally Clinic in September - November 2023. The population in the study were all post partum mothers at the Sally Medan Clinic. The results of this study indicate that the behavior of post partum mothers about baby massage the highest is behavior in the good category as many as 16 respondents (53.33%), sufficient behavior 11 respondents (36.67%) and less behavior 3 respondents (10%). The behavior of postpartum mothers about baby massage based on age was the highest at the age of 20-35 years as many as 26 people (86.67%), with good behavior as many as 14 respondents (46.67%), with sufficient behavior as many as 11 respondents (36.67%) and who behaved less 1 respondent (3.33%). The behavior of postpartum mothers about baby massage based on education is highest in high school education as many as 14 respondents (46.67%), while in the lowest group in junior high school with less behavior 1 respondent (3.33%). And the behavior of pregnant women based on parity was highest in multipara as many as 15 respondents (10%), who behaved well 8 respondents (26.66%), who behaved moderately 7 respondents (23.34%) and who behaved poorly there were none. From the results of this study it is hoped that mothers can improve their behavior about baby massage, and can do baby massage themselves at home.